Competency Profile of Football Coaches at PS Bintang Kejora Masbagik, East Lombok Regency - Lalu Sapta Wijaya Kusuma; Jamaludin Jamaludin; Elya Wibawa S; Kurnia Taufik; Nurdin Nurdin; Subakti Subakti (Abdi Masyarakat, 2026)
This community service activity aimed to map the competency profile of youth football coaches at SSB PS Bintang Kejora Masbagik, East Lombok Regency, with emphasis on coaching knowledge, self-assessment, and the practical application of sport science in training practice. This activity used a descriptive quantitative approach involving 10 coaches with different ages and coaching experiences. Data were collected using a questionnaire consisting of 10 knowledge questions related to football coaching and sport science, along with five self-assessment statements measured on a 1–5 scale. The results showed that the average knowledge score was 64%, indicating a moderate level of coach competence. The highest levels of understanding were found in the topics of hamstring injury, mental fatigue, and microcycle, whereas lower scores were found in Rating of Perceived Exertion, recovery nutrition, HR Max, and video analysis. The average self-assessment score was 3.8, indicating that coaches perceived their own competence as fairly good. However, the findings also revealed a gap between objective knowledge and self-perceived competence. These results indicate that further coach development programs are needed, particularly in training-load monitoring, recovery nutrition, physiological indicators, and simple video analysis, to support youth football training that is safer, more measurable, and evidence-informed.